2015
DOI: 10.1093/hmg/ddv083
|View full text |Cite
|
Sign up to set email alerts
|

HCFC1 loss-of-function mutations disrupt neuronal and neural progenitor cells of the developing brain

Abstract: Both gain- and loss-of-function mutations have recently implicated HCFC1 in neurodevelopmental disorders. Here, we extend our previous HCFC1 over-expression studies by employing short hairpin RNA to reduce the expression of Hcfc1 in embryonic neural cells. We show that in contrast to over-expression, loss of Hcfc1 favoured proliferation of neural progenitor cells at the expense of differentiation and promoted axonal growth of post-mitotic neurons. To further support the involvement of HCFC1 in neurological dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 38 publications
(75 reference statements)
11
64
0
1
Order By: Relevance
“…Recently, point mutations in HCF-1 were determined to be a basis for both neurological (X-linked Intellectual Disability) and biochemical (cblX) syndromes (Jolly et al, 2015; Yu et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, point mutations in HCF-1 were determined to be a basis for both neurological (X-linked Intellectual Disability) and biochemical (cblX) syndromes (Jolly et al, 2015; Yu et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…These male siblings also exhibited dysmorphic features and microcephaly. Experimental evidence from the examination of patient-derived cell lines and in vitro assays suggest that mutations within kelch domains result in almost complete loss of HCFC1 function and result in cobalamin disorder, while HCFC1 mutations in other regions result in much milder effects on protein function and cobalamin metabolism (8,10). Loss-of-function of the zebrafish homolog of HCFC1 has also been associated with craniofacial abnormalities through dysregulation of MMAHC (11).…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function of the zebrafish homolog of HCFC1 has also been associated with craniofacial abnormalities through dysregulation of MMAHC (11). It has been suggested that mutations in non-kelch domains of HCFC1, which result in partial loss-of-function, cause neurological disorders in the absence of cobalamin deficiency due to HCFC1 having other gene targets that are important for neurological development (8,10).…”
Section: Discussionmentioning
confidence: 99%
“…However, one might expect that the mechanistic basis of each disorder is completely unique because MMACHC is an enzyme in the cobalamin pathway (Hannibal et al, 2009) and HCFC1 is a transcriptional co-factor that regulates nearly 5000 different genes (Michaud et al, 2013, p. 1). In order to determine the distinct mechanisms regulating each phenotype, researchers have performed elegant functional analyses which have provided evidence that some phenotypes might be related, while others are likely completely unique (Gérard et al, 2015a, p. 1; Jolly et al, 2015, p. 1; Quintana et al, 2014, p. 1). These animal model studies substantiate clinical findings that demonstrate that a single treatment does not necessarily alleviate all phenotypes (Weisfeld-Adams et al, 2013).…”
Section: How Far Can Medical Genetics Take Us?mentioning
confidence: 99%